The humanity of Thucydides - Orwin, Clifford, 1947- (Princeton University Press, 1994)
Thucydides has long been celebrated for the unflinching realism of his presentation of political life. And yet, as some scholars have asserted, his work also displays a profound humanity. In the first thorough exploration of the relation between these two traits, Clifford Orwin argues that Thucydides' humanity is not a reflection of the author's temperament but an aspect of his thought, above all of his articulation of the central problem of political life, the tension between right and compulsion. This book provides the most complete treatment to date of Thucydides' handling of the problem of injustice, as well as the most extensive interpretations yet of the speeches in which it comes to light. Thucydides does not merely display the weakness of justice in the world, but joins his characters in exploring the implications of this weakness for our understanding of what justice is. Orwin pursues this question through Thucydides' work and relates it to the historian's other leading concerns, such as the contrast between the Athenian way and the Spartan way, the role of piety in political life, the interaction of foreign and domestic politics, and the role of statesmanship in a world dominated by frenzies of hope, fear, and indignation. Above all, Orwin demonstrates the richness, complexity, and daring of Thucydides' articulation of these issues.